2012
DOI: 10.5551/jat.11205
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe Oleracea (Açai) Modifies Sterol Metabolism and Attenuates Experimentally-Induced Atherosclerosis

Abstract: Aim: Euterpe oleracea (açai) is a fruit from the Amazon region whose chemical composition may be beneficial for individuals with atherosclerosis. We hypothesized that consumption of Euterpe oleracea would reduce atherosclerosis development by decreasing cholesterol absorption and synthesis. Methods: Male New Zealand rabbits were fed a cholesterol-enriched diet (0.5%) for 12 weeks, when they were randomized to receive Euterpe oleracea extract (n = 15) or water (n = 12) plus a 0.05% cholesterol-enriched diet for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
(15 reference statements)
3
13
0
2
Order By: Relevance
“…Moreover, it was demonstrated that C57BL/6 ApoA-I −/− mice developed NAFLD, suggesting that ApoA-I can be an important modulator of processes associated with deposition of lipids in the liver and development of diet-induced NAFLD. Our findings reinforce the notion of antiatherogenic effects of açai, as suggested elsewhere [84]. …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was demonstrated that C57BL/6 ApoA-I −/− mice developed NAFLD, suggesting that ApoA-I can be an important modulator of processes associated with deposition of lipids in the liver and development of diet-induced NAFLD. Our findings reinforce the notion of antiatherogenic effects of açai, as suggested elsewhere [84]. …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, anthocyanins may activate the AMPactivated protein kinase (AMPK) engaged in increasing skeletal muscle glucose uptake, reducing lipogenesis, promoting lipolysis and reducing cholesterol synthesis [46]. In agreement with our results, treatment with açai extract in male rabbits fed a diet enriched with 0.5% cholesterol for 12 weeks was effective in reducing triacylglycerol levels [48]. Emiliano et al, 2011 andResende et al, 2013 gave grape skin extract to rats fed a high fat diet during lactation, and they found that a dose of 200 mg/kg/day protected male and female offsprings from hypertriglyceridemia and enhanced glucose metabolism in adulthood [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…For the quantification of β-sitosterol and campesterol (markers of sterol absorption), as well as for desmosterol (a precursor of endogenous cholesterol synthesis), we used ultra-performance liquid chromatography (UPLC) and mass spectrometry (MS) as previously reported (18, 19). Briefly, the method consisted of liquid-liquid extraction followed by separation in the UPLC system and detection with an atmospheric pressure chemical ionization (APCI) ion source mass spectrometer operating on “single ion monitoring” for each sterol (β-sitosterol, campesterol, and desmosterol).…”
Section: Methodsmentioning
confidence: 99%